Optimization of microwave-assisted extraction to obtain a polyphenol-rich crude extract from duku (Lansium domesticum Corr.) leaf and the correlation with antioxidant and cytotoxic activities (Kuwait Journal of Science)
The present study employed microwave-assisted extraction (MAE) as a method to extract a crude extract high in polyphenols from the leaves of duku (Lansium domesticum Corr.), a medicinal plant indigenous to Indonesia. The study acquired data on the impact of various extraction parameters, such as ethanol concentration (X1), microwave power (X2), and extraction time (X3), on the levels of total phenolics content (TPC), total flavonoids content (TFC), and antioxidant activity using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. The extraction process was optimized using a Box-Behnken design (BBD) and response surface methodology (RSM). The optimal conditions were achieved with an X1 of 75%, an X2 of 315 W, and an X3 of 8.5 min. The aforementioned experimental settings yielded results of 86.176 mg GAE/g, 31.585 mg QE/g, and 75.850% for the TPC, TFC, and antioxidant activity, respectively. The extract included several significant active chemicals, including octadecanoic acid, undecane, 2-methyl-, 9-octadecenoic acid (Z)-hexyl ester, pentadecanoic acid, 9-hexadecanoic acid, phenolic and flavonoid compounds. The cytotoxic activity against MCF-7, T47D, and 4T1 cell lines was found to be slowed when exposed to crude extract doses ranging from 7.81 to 500.00 μg/mL. The present study's results suggest that MAE is a viable technique for extracting a polyphenol-rich crude extract from duku leaf. This extract shows promise as a natural antioxidant and has potential as an anti-breast cancer agent. © 2024 The Authors